Immunoglobulin A Nephropathy with Erythrocytosis: An Unusual Association - Navaradnam, Piratheepan (Cureus, 2021)
Immunoglobulin A (IgA) nephropathy is the commonest type of glomerular nephritis worldwide and is one of the leading causes of chronic kidney disease. Erythrocytosis is known to be associated with IgA nephropathy and other renal manifestations. We report a case of a 35-year-old male with grade 3 hypertensive retinopathy, erythrocytosis, and heavy proteinuria with an impaired renal function who was diagnosed as a case of erythrocytosis with IgA nephropathy and secondary focal segmental glomerulosclerosis. An extensive evaluation and prompt interventions significantly improved the outcome in this patient.